Pengaruh Lokasi dan Fasilitas terhadap Keputusan Pembelian Rumah pada Perumahan Green Rahayu Tahap 2 Setu Kabupaten Bekasi: The Influence of Location and Facilities on the Decision to Buy a House in Green Rahayu Housing Phase 2 Setu, Bekasi Regency - Melly Melly; Irwin Sukrisno Soegeng; Andri Rizko Yulianto (CV Warnak Johanna Nusantara, 2026)
This study aims to analyze the effect of location (X1) and facilities (X2) on the house purchase decision (Y) at Perumahan Green Rahayu Tahap 2 developed by PT Indo Megah Abadi in Setu District, Bekasi Regency, both partially and simultaneously. A quantitative method with a saturated sampling technique was applied to 100 consumers who had purchased a house in the housing complex. Data were collected via Likert-scale questionnaires and analyzed using multiple linear regression with SPSS 27. The t-test results show that location has a significant partial effect (t=6.785; Sig.=0.000), as does facilities (t=4.018; Sig.=0.000). The F-test indicates a significant simultaneous effect (F=34.284; Sig.=0.000). An R Square of 0.414 indicates both variables explain 41.4% of the variation in purchase decision. Location contributes more dominantly (28.09%) than facilities (9.86%). These findings enrich property marketing research in peri-urban areas that have not been widely studied.